Economic reforms in India: a sectoral analysis - Uppal, R. K. (ed.) (New Delhi, 2005)
"Responding to the macroeconomic crisis of the late 1980s, a programme of liberalisation, privatisation, and globalisation was initiated in India in July 1991. This programme encompassed wide-ranging reform measures touching almost every aspect of the Indian economy. s book explains the key reform measures undertaken in various sectors of the Indian economy since 1991. It examines their rationale, contents, and impact. Furthermore, the work puts in perspective the emerging lessons for the future. To provide the necessary backdrop to the new order, appropriate comparisons are made with the policies pursued prior to reforms period. "
Keywords: Economic reforms-India